The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1111/aor.12587
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia During Cardiopulmonary Bypass Increases Need for Inotropic Support but Does Not Impact Inflammation in Children Undergoing Surgical Ventricular Septal Defect Closure

Abstract: Minimizing the systemic inflammatory response caused by cardiopulmonary bypass is a major concern. It has been suggested that the perfusion temperature affects the inflammatory response. The aim of this prospective study was to compare the effects of moderate hypothermia (32°C) and normothermia (36°C) during cardiopulmonary bypass on markers of the inflammatory response and clinical outcomes (time on ventilator) after surgical closure of ventricular septal defects. During surgical closure of ventricular septal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Despite major improvements in circuit design, oxygenators and the advent of heparin-bonded surfaces, the inflammatory response to CPB remains a clinical concern. There have been several attempts to attenuate postoperative cytokine release including anti-inflammatory therapy 24 , modifications in the bypass circuit 25 or changing temperature management in CPB 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite major improvements in circuit design, oxygenators and the advent of heparin-bonded surfaces, the inflammatory response to CPB remains a clinical concern. There have been several attempts to attenuate postoperative cytokine release including anti-inflammatory therapy 24 , modifications in the bypass circuit 25 or changing temperature management in CPB 26 .…”
Section: Discussionmentioning
confidence: 99%
“…18,20 Furthermore, after enhancing the perfusion temperature, the effect of the hypothermic sympathetic response and increased blood viscosity on the hemodynamic effects weakens, resulting in the requirement of a higher dose of vasoconstrictors to maintain satisfactory perfusion pressure. 18,21 In contrast to hypothermic CPB, the increase in perfusion temperature may increase the effective dose of the anesthetic drug. 22 In 2011, a Canadian survey showed that more than 90% of institutions involved maintained a core temperature of 32-34℃ during CPB.…”
Section: Discussionmentioning
confidence: 99%
“…In the conditions of modern anesthetic technology and perfusion, a considerable amount of information has accumulated on various methods of preventing SIR, which are effective to a greater or lesser extent. We offer an overview of the most commonly used methods for the prevention of SIR (see Table 2) [43,[78][79][80][81][82][83][84][85][86][87][88][89].…”
Section: You Need To Know the Enemy By Sight Or How Not To Pass By De...mentioning
confidence: 99%